Work-in-Progress: HyFlex Hands-On Hardware Security Education During COVID-19 - Karam, Robert A.; Katkoori, Srinivas; Kermani, Mehran Mozaffari (2022 IEEE World Engineering Education Conference (EDUNINE), 2022)
Practical, hands-on hardware experience is an essential component of computer engineering education. Due to the COVID-19 pandemic, courses with laboratory components such as Computer Logic Design or FPGA Design were subject to interruption from sudden changes in course modality. While simulators can cover some aspects of laboratory work, they cannot fully replace the hands-on experience students receive working with and debugging hardware. For hardware security in particular, experimenting with attacks and countermeasures on real hardware is vital. In this paper, we describe our approach to designing a practical, hands-on hardware security course that is suitable for HyFlex delivery. We have developed a total of nine experiments utilizing two inexpensive, portable, and selfcontained development boards which generally obviate the need for bench equipment. We discuss the trade-offs inherent in the course and experiment design, as well as issues relating to deployment and support for the required design software.